Can Renewed Tensions of Tourist Areas Be Resolved? The Key Issue of Stakeholders’ Alignment - Caudan, Paul (E-Journal of Tourism; Volume 11 Number 1 (March 2024), 2024)
Tensions in tourist areas (over-visiting, waste management, traffic jams, conflicts of use, etc.) raise fundamental questions about sustainable development, the distribution of wealth, social justice, cultural identity and inclusion. Paradoxically, few decisions are taken to resolve these tensions, despite the dissatisfaction of all tourism stakeholders. The aim of this study is to help resolve the tensions in tourism areas by identifying a global method for aligning stakeholders. We conducted 72 interviews with all the tourism stakeholders in two very different tourist areas (Brittany and Bali) and used the concepts of sustainable tourism, stakeholders and strategic alignment. The results show that (1) the stakeholders, whether in favour of tourism development or not, all agree on the need to resolve the tensions in the tourist areas; (2) the obstacles and levers of the stakeholders play a decisive role in their commitment to collectively resolving the tensions in the tourist areas; (3) the existing data on tourist numbers are the subject of debate among the stakeholders and slow down the commitment to concrete action. Our conclusions are encouraging, since tensions in tourist areas constitute a problem like any other, which makes it possible to envisage a global methodology for aligning stakeholders. However, the subject of tourist numbers remains a stumbling block in the project to resolve tourism tensions in these areas. Three avenues of research are proposed to help overcome this dead end: integrating the notion of perceived value into measures of tourist numbers in tourist areas, mobilising participatory science to increase the potential of measures of tourist numbers, and adapting the technological acceptance model to tourist numbers.